Aukus (Australia-united kingdom-united states) threat to Indo-pacific security - Ismiyatun Ismiyatun; Ita Puji Lestari (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The Indo-Pacific region, as the fastest-growing and economically significant area in the world, is increasingly becoming a focal point of geopolitical tensions, particularly with the emergence of the AUKUS alliance. The introduction of nuclear-powered submarines by Australia under AUKUS presents a profound threat to the stability and security of the Indo-Pacific, challenging existing treaties like the Southeast Asia Nuclear Weapon Free Zone (SEANWFZ) and potentially igniting an arms race. Understanding these dynamics is critical for shaping policies that can mitigate the risks of escalating military conflicts and ensure regional stability. The primary objective of this study is to critically analyze the security implications of the AUKUS alliance on the Indo-Pacific region, with a particular focus on how the introduction of nuclear-powered submarines by Australia could undermine regional treaties and provoke an arms race. This study employs a qualitative research approach, specifically using the method of a literature review. The data sources for this study consist of secondary data, including academic journal articles, books, governmental and non-governmental reports, and policy briefs. Data collection was conducted by systematically searching for relevant literature using keywords such as